Oil and gas corrosion prevention : from surface facilities to refineries - Speight, James G. (Gulf Professional, 2014)
According to NACE (National Association of Corrosion Engineers), the total annual cost of corrosion in petroleum refining takes up 3.7 billion in the US alone. Corrosion control is always a challenge for the downstream industry, but as the quality of feedstock is declining due to refineries accepting more of the heavy and shale gas and oil resources that are more readily available today, refinery managers, petroleum and natural gas engineers are unprepared for the new set of corrosion problems that are showing up in their equipment and processing units.